Stochastinių logistinių augimo modelių su vėlinimu apytiksliai stacionarieji sprendiniai ir parametrų įvertinimai L1 atstumo metodu - Rupšys, Petras (Lietuvos matematikos rinkinys, 2007)
We consider stochastic logistic type delayed growth model (Verhulst, Gompertz, Richards) of a single species population.The objective of this paper is to deduce a procedureon the estimation of parameters. We derive approximate stationary distributions in the case of small time delays. For the estimate of parameters we apply the L1 distance procedure. We propose approximate estimations of the parameters.